A Study of the Effects of Competence, Work Discipline, and Loyalty on Employee Performance at the Solok City Agriculture and Food Service - Gusti Wardana, Tisa; Yeni, Afni; Nurhayati, Nurhayati (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to determine the influence of competence, loyalty, and work discipline on employee performance at the Solok City Agriculture and Food Service Office. The research employed a quantitative approach with a sample of 110 respondents. The results of the t-test indicate that competence (X1), work discipline (X2), and loyalty (X3) significantly affect employee performance. Statistical analysis shows that competence (X1) has a significant effect on employee performance, with a calculated t-value of 2.257 > t-table 1.982 and a significance value of 0.026 < 0.05. Therefore, employee performance is strongly influenced by competence. Furthermore, work discipline (X2) also has a significant effect on employee performance, with a calculated t-value of 3.502 > t-table 1.982 and a significance value of 0.001 < 0.05. This finding indicates that employee performance is greatly influenced by work discipline. In addition, loyalty (X3) significantly affects employee performance, with a calculated t-value of 2.759 > t-table 1.982 and a significance value of 0.007 < 0.05. Thus, employee performance is also significantly influenced by loyalty. At the Solok City Agriculture and Food Service Office, competence, work discipline, and loyalty collectively have a substantial impact on employee performance. This is supported by the results of the F-test, which show an F-calculated value of 31.956 > F-table 2.690 and a significance value of 0.000, which is lower than α (0.05). The coefficient of determination (R Square) value of 0.475 indicates that competence, work discipline, and loyalty contribute 47.5% to employee performance, while the remaining 52.5% is influenced by other factors not examined in this study.